STRATEGI PENGENDALIAN TERHADAP POLUSI AIR SUNGAI DI SUB-DAS RIAM KIWA KABUPATEN BANJAR - Syaiful Bahri; Syarifuddin Kadir; Suyanto Suyanto; Emmy Lilimantik (Universitas Lambung Mangkurat, 2019)
The Sub-DAS Riam Kiwa is a tributary of the Martapura upstream, which is often used by the community to cover daily needs such as cooking, washing, and latrines. The current quality of water condition of the Sub-DAS Riam Kiwa is estimated to have decreased caused by various human activities on the riverbank. This study aims to determine the strategy of controlling river water pollution. The river as a research area is set at 24.4 km. Water quality was measured and observed at 3 sampling points then analyzed using the Pollution Index method. Analysis of water pollution control strategies was using SWOT Analysis. The results showed that the Sub-DAS Riam Kiwa was classified as moderately polluted with an IP value from upstream to downstream of 7.88; 8.92; and 9.38. To maintain water quality in natural conditions a water pollution control strategy is needed through diversification of existing strategies or programs as a result of 1) strong internal factors including the monitoring of water quality, water quality standards; and 2) the many threats from external factors which include the disposal of domestic waste and livestock without recycling, the community does not have the knowledge of waste and the community often violates government regulations.